VET teachers in Europe: policies, practices and challenges - Misra, Pradeep Kumar [Verfasser] (My University, 2011)
"The objective of making vocational education and training (VET) globally competitive and attractive by the European Union has put vocational teachers in the spotlight. As a result, the VET teacher profession in Europe is facing many challenges and demands expressed constantly by the general public, representatives from the world of work, public authorities and political decision-makers. On the other side, VET teachers are often overshadowed by their counterparts in general education as societies place greater emphasis on academic education and credentials. With this backdrop, the paper provides an outline of the VET teacher training system in European member states; it attempts to understand VET teacher training in European countries, analyses the different policies and approaches adopted in Europe to train VET teachers, reflects upon core VET teacher training challenges in Europe, discusses the professionalisation of VET teacher issues, and suggests initiatives for the continuous professional development of VET teachers with a hope that 'European and other societies will offer due recognition to competent VET teachers who are constantly producing a qualified VET workforce for a better world economy'."
Keywords: P 3.2.3 Lehrer; P 3.2.2 Weiterbildner; I 2.2 Europa; Berufsschullehrer; Weiterbildner; Lehrerausbildung; Lehrerfortbildung; Professionalisierung; Internationaler Vergleich; Europa